The impact of China's zero-COVID policy on stock returns - Wenwen Luo; Wojtek Paczos (Cardiff University, Cardiff Business School, 2025)
This study examines the impact of China's "Zero-COVID" policies on stock returns in the healthcare sector from January 2020 to December 2022. Using panel regression analysis, we find that increases in the Stringency Index increased healthcare stock returns. In contrast, vaccination rates are associated with a decline in returns when averaged across the full sample. However, a time-disaggregated analysis reveals heterogeneity: in the period of the initial vaccine rollout, vaccination had a statistically significant positive effect, while in the later period, the relationship turned negative. The interaction analysis indicates that the effect of stringency on returns was stronger and the effect of vaccinations was weaker when the number of new cases of COVID-19 was high. These findings indicate that investor responses were nonlinear and evolved over time, reflecting changing expectations around pandemic control.
Keywords: G12; E65; C23; I18; 330; Stock Returns; Zero-COVID Policy; Healthcare Sector